16th IHIW: Immunogenomic Data‐Management Methods. Report from the Immunogenomic Data Analysis Working Group (IDAWG). (26th December 2012) - Hollenbach, J. A.; Holcomb, C.; Hurley, C. K.; Mabdouly, A.; Maiers, M.; Noble, J. A.; Robinson, J.; Schmidt, A. H.; Shi, L.; Turner, V.; Yao, Y.; Mack, S. J.
<x xml:space="preserve">Abstract</x> Summary The goal of the immunogenomic data analysis working group (IDAWG) is to facilitate the consistent analysis of HLA and KIR data, and the sharing of those data among the immunogenomic and larger genomic communities. However, the data management approaches currently applied by immunogenomic researchers are not widely discussed or reported in the literature, and the effect of different approaches on data analyses is not known. With ASHI's support, the IDAWG developed a 45 question survey on HLA and KIR data generation, data management and data analysis practices. Survey questions detailed the loci genotyped, typing systems used, nomenclature versions reported, computer operating systems and software used to manage and transmit data, the approaches applied to resolve HLA ambiguity and the methods used for basic population‐level analyses. Respondents were invited to demonstrate their HLA ambiguity resolution approaches in simulated data sets. By May 2012, 156 respondents from 35 nations had completed the survey. These survey respondents represent a broad sampling of the Immunogenomic community; 52% were European, 30% North American, 10% Asian, 4% South American and 4% from the Pacific. The project will continue in conjunction with the 17th Workshop, with the aim of developing community data sharing standards, ambiguity resolution documentation formats, single‐task data Management tools and novel data analysis methods and applications. While additional project details and plans for the 17th IHIW will be forthcoming, we welcome the input and participation in these projects from the histocompatibility and immunogenetics community.